Tony Fretton Architects : buildings and their territories - Tony Fretton Architects; Buxton, Pamela; Fretton, Tony (Basel, SZ. : Birkhauser, 2014)
A comprehensive overview on the work of renowned London architect Tony Fretton. After graduating from the reputable Architectural Association in 1982 Fretton opened his own architect's office. He attracted attention early on with the Lisson Gallery and the'Red House' (London). His spatial creations and their incorporation into the urban context are of subtle mastery. With his designs for the Camden Arts Centre, the Fuglsang Kunstmuseum in Denmark, London townhouse for the artist Anish Kapoor and the British Embassy in Warsaw, Fretton has emerged as one of the most prominent contemporary architects. This monograph provides a long-awaited reference work to his oeuvre.
Keywords: Fretton, Tony; Tony Fretton Architects; Architectural firms -- United Kingdom; Architecture, Modern -- 21st century; Architecture -- United Kingdom -- History -- 20th century; Architecture -- United Kingdom -- History -- 21st century